2022
DOI: 10.1364/josab.446013
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent and angle-insensitive absorber with hyperbolic material

Abstract: A polarization-dependent and angle-insensitive absorber based on surface phonon polaritons (SPhPs) is proposed based on a sandwiched layer structure that consists of a patterned α - M o O 3 layer, a dielectric layer, and a gold layer. The absorption remains larger than 95% for TE incidence wave with incident angles from 0° to 30° in the wavelength range from 13.7 to 18.3 µm, which is a broadband absorber. At the same tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For example, Sui et al demonstrated an a-MoO 3 metasurface absorber based on surface phonon polaritons with polarization-dependent and angle-insensitive absorption properties in the mid-infrared band. 45 Currently, the understanding of the light-matter interaction in a-MoO 3 is still in its nascent stages, and there is limited research on a-MoO 3 based electromagnetic absorbers, particularly those exhibiting polarization-dependent perfect absorption. However, the exploration of such absorbers holds immense importance for various applications like photodetectors, optical communication, and technical inspection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sui et al demonstrated an a-MoO 3 metasurface absorber based on surface phonon polaritons with polarization-dependent and angle-insensitive absorption properties in the mid-infrared band. 45 Currently, the understanding of the light-matter interaction in a-MoO 3 is still in its nascent stages, and there is limited research on a-MoO 3 based electromagnetic absorbers, particularly those exhibiting polarization-dependent perfect absorption. However, the exploration of such absorbers holds immense importance for various applications like photodetectors, optical communication, and technical inspection.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, α-molybdenum trioxide (α-MoO 3 ) exhibits phonondriven NBHM behaviour in the long-wavelength mid-infrared range, making it a promising candidate for creating optical components with superior efficiency. [30,31] α-MoO 3 , a type of van der Waals crystal with orthorhombic unit cells, shows a biaxial hyperbolic anisotropy in the mid-infrared part of the electromagnetic spectrum. [32,33] The inherent anisotropy of α-MoO 3 , arising from its distinctive crystalline structure, results in natural in-plane hyperbolic characteristics that stem from the interplay between the lattice modes and three crystal directions that are orthogonal to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbolic materials are extreme anisotropic materials, whose permittivity tensor has diagonal elements of not all the same sign. [1][2][3][4][5][6] They can support high-wavevector propagating waves and possess distinctive properties different from that of conventional materials, and thus they have attracted significant attention over the past few years. [7][8][9][10][11][12][13] So far, hyperbolic polaritons (HPs) have been discovered in natural hyperbolic materials, such as hexagonal boron nitride (hBN) and alpha-phase molybdenum trioxide (α-MoO 3 ).…”
Section: Introductionmentioning
confidence: 99%